(untitled) (Atti del Sodalizio Glottologico Milanese, 2017)
The present work compares the verbal endings of the singular of some ancient I.E. languages showing how they point to a concatenative - agglutinative type. It is furthermore suggested that the original PIE morpheme of the third person singular of the series of endings developing into middle and perfect is to be reconstructed as *-h1. KEYWORDS: Proto-Indo-European linguistics, historical morphology, Proto-Indo-European verbal morphology, Proto-Indo-European verbal endings